Interleukin-10 Is a Natural Suppressor of Cytokine Production and Inflammation in a Murine Model of Allergic Bronchopulmonary Aspergillosis - Grünig, Gabriele (The Rockefeller University Press, 1997)
We have used interleukin-10 (IL-10) gene knockout mice (IL-10(−/−)) to examine the role of endogenous IL-10 in allergic lung responses to Aspergillus fumigatus Ag. In vitro restimulated lung cells from sensitized IL-10(−/−) mice produced exaggerated amounts of IL-4, IL-5, and interferon-γ (IFN-γ) compared with wild-type (WT) lung cells. In vivo, the significance of IL-10 in regulating responses to repeated A. fumigatus inhalation was strikingly revealed in IL-10(−/−) outbred mice that had a 50–60% mortality rate, while mortality was rare in similarly treated WT mice. Furthermore, IL-10(−/−) outbred mice exhibited exaggerated airway inflammation and heightened levels of IL-5 and IFN-γ in bronchoalveolar lavage (BAL) fluids. In contrast, the magnitude of the allergic lung response was similar in intranasally (i.n.) sensitized IL-10(−/−) and wild-type mice from a different strain (C57BL/6). Using a different route of priming (intraperitoneal) followed by one i.n. challenge we found that IL-10(−/−) C57BL/6 mice had heightened eosinophilic airway inflammation, BAL–IL-5 levels, and numbers of αβT cells in the lung tissues compared with WT mice. We conclude that IL-10 can suppress inflammatory Th2-like lung responses as well as Th1-like responses given the constraints of genetic background and route of priming.